Ifosfamide, epirubicin and cisplatin (IEP): another active combination for small cell lung cancer (SCLC) - Thongprasert S. (2014)
Sixty-four SCLC patients (44 males and 20 females, median age 60 years, median PS 60%) were treated with an IEP regimen. Forty-nine cases were evaluable, 35 cases were limited disease (LD) and 14 cases were extensive disease (ED). Treatment consisted of ifosfamide 1.5 g/m2 i.v. infusion for 4 h on days 1 and 2 with mesna uroprotection; epirubicin 60 mg/m2 i.v. on day 1; and cis-platin 60 mg/m2 i.v. infusion over 2 h on day 3; repeated treatment every 4 weeks. Eighty percent response rate (95% confidence limit = 66.75% to 93.25%) was seen in LD with 22.8% CR. In ED, total response rate was 85.7% (95% confidence limit = 67.36% to 104.04%) with 21.4% CR. One-year survival of LD was 45.5% and ED was 17.6%. Treatment toxicity was moderate. Most common toxic effects included alopecia, leukopenia (28.5% grade 3, 14.3% grade 4) nausea and vomiting (50% grade 2, 15% grade 3) and anemia (26.5% grade 3 and 4). Addition of thoracic radiotherapy after complete chemotherapy (only CR and PR in LD cases) was a good prognostic factor. These results suggest that IEP regimen is one of the active combination for SCLC. The dosage of IEP in this study caused moderate toxicity.